1998
DOI: 10.1074/jbc.273.43.28346
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of αB-crystallin in Mitotic Cells and Identification of Enzymatic Activities Responsible for Phosphorylation

Abstract: The immunofluorescence localization of ␣B-crystallin in U373 MG human glioma cells with an antibody specific for ␣B-crystallin that had been phosphorylated at Ser-45 revealed an intense staining of cells in the mitotic phase of the cell cycle. Phosphorylated forms of ␣B-crystallin in mitotic cells were detected in all cell lines examined and in tissue sections of mouse embryos. Increases in the levels of ␣B-crystallin that had been phosphorylated at Ser-45 and Ser-19, but not at Ser-59, were detected biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 33 publications
3
118
0
1
Order By: Relevance
“…Instead, despite absence of ischemia-induced HSP25 phosphorylation in MK2 −/− hearts, infarct size was similar to that in MK2 +/+ hearts, implying that HSP25 phosphorylation is not critical to outcome in ischemia. Earlier studies had indicated that activation of p38 MAPK and MK2 are necessary for the phosphorylation of αB-crystallin on Ser-59 (Kato et al 1998;Ito et al 1997). In the absence of MK2, phosphor- ylation of αB-crystallin on Ser-59 was reduced in response to ischemia but was not completely abolished, implying that other kinases may act in concert with MK2 to achieve maximal αB-crystallin phosphorylation.…”
Section: Effect Of Mapkapk-2 Deficiency and Sb203580 On Downstream Simentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, despite absence of ischemia-induced HSP25 phosphorylation in MK2 −/− hearts, infarct size was similar to that in MK2 +/+ hearts, implying that HSP25 phosphorylation is not critical to outcome in ischemia. Earlier studies had indicated that activation of p38 MAPK and MK2 are necessary for the phosphorylation of αB-crystallin on Ser-59 (Kato et al 1998;Ito et al 1997). In the absence of MK2, phosphor- ylation of αB-crystallin on Ser-59 was reduced in response to ischemia but was not completely abolished, implying that other kinases may act in concert with MK2 to achieve maximal αB-crystallin phosphorylation.…”
Section: Effect Of Mapkapk-2 Deficiency and Sb203580 On Downstream Simentioning
confidence: 99%
“…Activated p38 MAPK phosphorylates nuclear MK2 and forms a complex whereby an MK2 nuclear export signal is unmasked, resulting in its rapid export from the nucleus (Maulik et al 1996;Engel et al 1995;Ben Levy et al 1998). In the cytoplasm, MK2 phosphorylates the small heat shock proteins (HSP) 25/27 (Stokoe et al 1992;Freshney et al 1994;Rouse et al 1994) and αB-crystallin (Hoover et al 2000;Ito et al 2001;Kato et al 1998). The phosphorylation of HSP25/27 induces its dissociation from large aggregates into dimers and monomers (Kato et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bc is phosphorylated at three serine residues, Ser19, Ser45 and Ser59 [118,120,121]; phosphorylation at Ser45 is mediated by p44/p42 MAPK, at Ser59 by MAPKAPK-2 [118,122], whilst the kinase responsible for phosphorylation at Ser19 remains to be identified. Similarly, Hsp27 has three serine residues (Ser15, Ser78 and Ser82) that undergo phosphorylation [123,124].…”
Section: Phosphorylationmentioning
confidence: 99%
“…Both inside and outside the lens, the major post-translational modification described for αB-crystallin and Hsp25 is phosphorylation at three serine residues; in αB-crystallin these are S19, S45 and S59 (S15, S78 and S82 in Hsp27) [111][112][113][114]. Various types of cellular stress, such as heat, oxidation and increased intracellular calcium levels, stimulate the phosphorylation of sHsps [111].…”
Section: The Effect Of Post-translational Modifications On the Chapermentioning
confidence: 99%